Understanding Multiple Dimensions of Perceived Greenspace Accessibility and Their Effect on Subjective Well-Being During a Global Pandemic - Maurer, Megan; Cook, Elizabeth M.; Yoon, Liv; Visnic, Olivia; Orlove, Ben; Culligan, Patricia J.; Mailloux, Brian J. (Frontiers in Sustainable Cities, 2021)
The COVID-19 pandemic has demonstrated how the accessibility of greenspace can shift in response to social-ecological disturbance, and generated questions as to how changing dimensions of accessibility affect the ecosystem services of greenspace, such as improved subjective well-being. Amidst the growing consensus of the important role of greenspace in improving and maintaining well-being through times of duress, we examine how access to greenspace is affecting subjective well-being during the COVID-19 pandemic. Both the relationship of greenspace to subjective well-being and the barriers to greenspace access are well-established for normal conditions. Much remains to be known, however, about how barriers to access and the effect of greenspace on subjective well-being shift in response to periods of social duress, such as the current COVID-19 pandemic. Using data from surveys and interviews conducted with 1200 university students in the United States during the spring of 2020, we assess the effect of going outdoors on subjective well-being, commonly experienced barriers to going outside, and how these barriers in turn affected subjective well-being. We find that time spent outside, particularly in greenspace, correlates with higher levels of subjective well-being, and that concern over COVID-19 risk and transmission negatively affects this relationship both in reducing time spent outdoors and the subjective well-being benefits. We also find that type of greenspace (public versus private) does not have a significant effect on subjective well-being, and that while those in areas with lower population density have significantly higher subjective well-being when outdoors, all participants experience a statistically equal benefit to subjective well-being by going outside. Our findings suggest how understanding the ways dimensions of accessibility shift in response to times of social duress can aid public health messaging, the design and management of greenspace, and environmental justice efforts to support the use of greenspace in improving and maintaining subjective well-being during future crisis events.